Humoral Immunity Assessment in Calves Born to Cows Immunized with Inactivated Vaccine for Bovine Herpesvirus 1 and Bovine Viral Diarrhea Virus - Viviani Gomes (Acta Scientiae Veterinariae, 2014)
Background: Considering that calves are immunologically immature at birth, maternal vaccination at the precalving period has been used as an alternative approach to increase the antibody titers in the colostrum, providing better immunological assistance to neonates. This study aimed to evaluate the influence of maternal immunization with inactivated vaccine for Bovine Herpesvirus type I (BoHV-1) and Bovine Viral Diarrhea virus (BVDV) at the precalving period on the transfer of passive immunity to calves. Material, Methods & Results: Eleven pregnant cows were divided into non-vaccinated (C, control; n = 4) and vaccinated (VAC; n = 7) groups. The vaccinated cows were seronegative for BVDV, but two animals of the control group presented titers for BoHV-1 due to natural exposure. The immunization was performed at 60 and 30 days precalving by using a commercially available vaccine from Argentine that consisted of inactivated strains of BVDV-1, BVDV-2, and BoHV-1. Calves were fed 4 L of colostrum in the first 12 h after birth. Colostrum and blood samples were collected from calves before (T0) and after colostrum feeding up to 15th day (T1-T6). Specific antibodies (ABs) in the colostrum and serum were detected using serum neutralization (SN) test. At T0, AB titers for BVDV and BoHV-1 were not detected in the blood serum of calves. Only one cow from the VAC group had ABs for BVDV in the colostrum, and its calf showed seroconversion after receiving passive immunity. The remaining colostrum and serum samples of calves from the VAC and C groups yielded negative results in the SN test (T0 to T6). Detecting ABs in the colostrum for BoHV-1 was not possible due to its toxicity to the cell culture used in SN; however, the serum of VAC neonates (100%) yielded positive results from T1 to T6. The AB titers (range, 16-1024) and geometric mean titers (GMTs) for BoHV-1 in the serum of VAC calves were absent from the 1st to 15th day of life after colostrum feeding in the control group, AB titers were observed in the serum of two of four calves that were born to non-vaccinated cows that showed positive results due to natural exposure to BoHV-1. The log2 GMTs (5.14-5.86) from VAC calves were higher than those in the control calves (log2 GMTs = 1.75-2.25). Discussion: Cows immunized during the precalving period showed poor response to BVDV and passive transfer of antibodies to their calves. Inactivated vaccines could be safely used in the pregnant cows, but they had low intensity and short-term efficacy. Further, maternal vaccination schedules need to be decided appropriately since cows show immunosuppression during the precalving period. For BoHV-1, seroconversion was noted in all the calves fed colostrum, suggesting that immunized cows had neutralizing ABs in their mammary secretion. Seronegative and non-vaccinated cows did not transfer ABs for BVDV and BoHV-1 to their calves. Naturally exposed seropositive cows and non-vaccinated (C) cows transferred ABs to their calve